TASK-BASED SYLLABUS DESIGNS AND COGNITIVE ASPECTS IN L2 PERFORMANCE - Bergsleithner, Joara Martin (Revista ECOS, 2019)
This article reviews some issues on cognitive aspects of task-based syllabus designs, particularly based on two studies (ROBINSON, 2001; SKEHAN & FOSTER, 2001) that deal with cognitive accounts of task-based designs. First, I will focus on contrasting positions of these two papers concerning attentional resources. Second, I will present some empirical results of studies on the effects of task difficulty and conditions. Third, I will show pedagogic sequencing of tasks. Fourth, I will display the measures of three dimensions of task performance, and the measures of task difficulty. Finally, I will close the article with a call for longitudinal studies to investigate second language performance and learning.